Social protection and cash transfers to strengthen families affected by HIV and AIDS - Adato, Michelle; Bassett, Lucy (International Food Policy Research Institute, 2012)
As HIV and AIDS simultaneously undermine livelihoods and household and community safety nets, families are especially vulnerable to poverty, food insecurity, and threats to their children’s nutrition, health, and education, with irreversible consequences. With more than 33.3 million people affected by HIV globally, a new focus on the risks for families and the long-term well-being of children has accelerated international, regional, and national commitments to social protection programs in heavily AIDS-affected countries.